Analytical modelling of podium interference on tower walls in buildings. Issue 4 (2nd October 2017) - Yacoubian, Mehair; Lam, Nelson; Lumantarna, Elisa; Wilson, John L.
ABSTRACT: In regions of low-to-moderate seismicity like Australia, a common form of building construction is the one featuring a podium structure that supports a tower with smaller floor plan. This building layout is particularly favoured in metropolitan regions as it can cater for a mix of commercial and residential functionalities. This paper investigates the undesirable effects of podium interferences on the shear demands on the structural walls at and above the interface zone. Shear force redistributions between the connected structural walls were found to be the direct consequence of the differential restraints imposed by the podium structure. The generation of in-plane strutting forces in the slabs and beams connecting the structural walls was also found to be proportional to the extent of the deformation incompatibility between the walls and columns above the podium level. An analytical model is proposed herein for estimating in-plane strutting forces in the connecting slabs (or beams). The model has been verified against results obtained from finite element analyses using 2D, and 3D, sub-assemblages of the building. Deficiencies in the conventional diaphragm modelling approaches have been highlighted, and optimal solutions are proposed.